Historiography of the Study of Bulgarian-Tatar Epigraphic Monuments and Modern Research Methods - Khamidullin S.R; Gainutdinov А.М.; Gainullin I.I.; Abdullin Kh.М.; Kasimov А.V. (Золотоордынское обозрение)
The purpose of the study is to trace the historiography of the study of the Bulgarian-Tatar epigraphic monuments in the vast Zakazanye region of the Republic of Tatarstan, as well as to show the possibilities of modern research methods in this matter. Research materials: Bulgarian-Tatar epigraphic monuments (tombstones) of the 13th–17th centuries. The work also involves extensive data from the historiography of the study of Bulgarian-Tatar epigraphic monuments and the results of modern methods of studying epigraphic monuments. Results and novelty of the research: In chronological order, a review of the history of the study of the Bulgarian-Tatar epigraphic monuments in the Zakazanye region from the first researchers’ arrival to the ongoing research that is being carried out presently. The data on the specific personalities of researchers and quantitative data of the studied epigraphic monuments by the areas of the Zakazanye region are provided. The modern methods of studying the epigraphic monuments of the Bulgar-Tatar period, including 3D scanning, photogrammetry, and high-precision photofixation with the placement of digital copies of monuments on a web resource, are shown. Within the framework of this study, surveys of epigraphic monuments were conducted for the first time at the modern methodological and technical level. Thanks to the results of high-precision photogrammetric photography and 3D modeling, it was possible to obtain digital copies of objects which makes it possible to determine changes in shapes, as well as to restore the shape of lost objects from archival data.